Investigation of measurement-computing procedures primary system informational transformation of stochastically non-stationary vibrosignals - O. Yu. Kropachek (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Measuring signals reflecting local processes of complex industrial aggregates bear important information about the long-term functional stability of such dynamic objects. However, to detect such information in signals with a priori unknown probability models of nonstationarity is a problem. It's possible solution is the creation of information technologies for the parametrization and normalization of random spectral changes in signals with significant limitations on the observation time. Such technologies will reduce the risks of decision making during monitoring and diagnosing of functional conditions of industrial, transportation, and process facilities. The identification of regularities in random models of nonstationarity is the acquisition of fundamentally new additional information on the functional properties of a dynamic object that facilitates the solution of many problem identification problems of objects and the optimal synthesis of information computerized systems under conditions of a priori uncertainty.